2018
DOI: 10.1038/s41598-018-35762-0
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of a leguminous shrub to a rubber plantation changed the soil carbon and nitrogen fractions and ameliorated soil environments

Abstract: The conversion of monoculture rubber (Hevea brasiliensis) plantations into rubber-based agroforestry systems has become a common trend in forestry management in the past few decades. Rubber–Flemingia macrophylla (a leguminous shrub) systems are popular in southwestern China’s Xishuangbanna region. The biogeochemical cycles of soil carbon and nitrogen in forests are mainly affected by their fractions. This study investigated the effect of introducing Flemingia macrophylla to rubber plantations of different ages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Accordingly, the CAISPP values showed that of intercropped RPs had better soil quality than monoculture RPs. These findings show that, consistent with some previous studies (Chen et al, 2019;Liu, Nie, et al, 2018;Liu et al, 2019), intercropping improves soil quality in RPs.…”
Section: Effects Of Intercropping On Soil Physicochemical Properties In Rpssupporting
confidence: 93%
See 1 more Smart Citation
“…Accordingly, the CAISPP values showed that of intercropped RPs had better soil quality than monoculture RPs. These findings show that, consistent with some previous studies (Chen et al, 2019;Liu, Nie, et al, 2018;Liu et al, 2019), intercropping improves soil quality in RPs.…”
Section: Effects Of Intercropping On Soil Physicochemical Properties In Rpssupporting
confidence: 93%
“…The continuously rising need of RPs is accompanied by the conversion of tropical forests into RPs in tropical Asia (Allen et al, 2015;De Blécourt et al, 2014;Guillaume et al, 2018;Hassler et al, 2017). Generally, this conversion has negative impacts on soils and ecosystem services, threatening biodiversity and human livelihoods (Liu, Nie, et al, 2018;Liu et al, 2019;Qiu, 2009;Tan et al, 2011;Zhai et al, 2012Zhai et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…poeppigiana (poró) and the majority of Inga species. These species make up the most abundant agroforestry trees in coffee and cocoa plantations in Mesoamerica 31,32 , and have a key role for the management of soil fertility and sustain more stable productivity 33,34 , especially in low-input and small farming plantations 35 . Therefore, our results anticipate a serious threat for future coffee and cocoa plantations if alternatives for N -fixing species are not promptly identified.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an environmentally friendly rubber plantation construction has been initiated in Xishuangbanna, and several combinations of rubber trees and other economic plants in agroforestry systems have been tried (Liu et al 2016a;Mo and Sha 2016). In these systems, some understory plants, such as Flemingia macrophylla (Liu et al 2018;Pang et al 2009), produce waste biomass after clipping every year which could be used to make biochar. Other potential feedstocks in the Xishuangbanna area, such as corn stalks and coconut shells, are also available for biochar production.…”
Section: Potential For Biochar Addition In Rubber Plantationsmentioning
confidence: 99%